Rotation and rotation-annihilation construction of associative and partially compensatory aggregation operators. - Jenei, S.
In this paper, it is shown that aggregation operators cannot be associative and strictly compensatory at the same time. As a way out, the rotation construction and the rotation-annihilation construction are applied to construct wide classes of associative aggregation operators that are compensatory on a subdomain only. From this point of view, the resulting operators are similar to uninorms, a class of aggregation operators that is being reported on extensively in the literature. The constructions are demonstrated by means of ample examples.
Keywords: Associative aggregation operator; Compensatory aggregation operator; Rotation annihilation construction